Pengaruh Inovasi Financial Technology, Influencer Media Sosial, dan Locus of Control Terhadap Minat Investasi Generasi Z - Putra, Dicky Pratama; Priyono, Achmad Agus; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of fintech innovation, social media influencers, and locus of control on investment interest of generation Z. The quantitative method was used with a survey of 90 FEB UNISMA students of class of 2021 selected through purposive sampling. Data analysis used SPSS 27 software. The research instrument has passed the validity and reliability test. The analysis was carried out using multiple linear regression. The results showed that fintech innovation and social media influencers have a significant positive effect on investment interest. Conversely, locus of control has no significant effect. This research model is simultaneously significant with a coefficient of determination of 0.567 so that 56.7% of the variation in investment interest can be explained by the independent variables. Keywords: Financial Technology Inovation, Media Social Influencers, Locus of Control, Investment Interest